Synthesis, Isolation and Characterization of Process-Related Impurities in Salbutamol Sulphate - Yogesh Kumar Sharma; Dau Dayal Agarwal; Sudesh Bhure; Rajendra Nath Mukharjee; Pramod Kumar Sahu; Santosh Bhardwaj (E-Journal of Chemistry)
Three known and one unknown impurities in salbutamol sulphate bulk drug at level 0.1% (ranging from 0.05-0.1%) were detected by gradient reverse phase high performance liquid chromatography. These impurities were preliminarily identified by the mass number of the impurities. Different experiments were conducted and finally synthesized and characterized the known and unknown imputities.